(untitled) (American Journal of Islam and Society, 2008)
On 17 October 2008, the Academy of Islamic Studies held its first seminar on Na`ar¥yOEt al-îukm and Ma§OEdir al-Shar¥`ah (NAZMAS1/2008) at the University of Malaya, Kuala Lumpur, Malaysia. We would like to thank all of the lecturers and students of the Department of Shari`ah and Law, especially Ahmad Hidayat Buang (dean of the Apium) and Siti Mashitoh bt Mahamood (head, Department of Shari`ah and Law), for their support and encouragement. The seminar originally sought to bring together students, researchers, and scholars interested in Islamic law studies from all over the world. Due to the limited time available for academicians and scholars to prepare their papers, as well as holding it right after Ramadan, however, was the event to be scaled down to a local seminar limited to the Academy of Islamic Studies, University of Malaya. It was, nevertheless, a highly fruitful and successful event. Given the international focus on Islamic studies and law, the seminar was structured around the fundamental principles of Islamic law and how they can be embraced by elaborating upon their vital principles to make them better understood. After the chairmen’s introductory remarks, seminar director Saim Kayadibi (senior lecturer, Department of Shari`ah and Law) gave an opening speech that emphasized the importance of studying the Shari`ah’s fundamental principles and how the seminar could make a constructive contribution to advancing the participants’ knowledge and understanding of the inner dimension of the aúkOEm and ma§OEdir al-Shar¥`ah. Mahamood then opened the seminar ...